A 150-Year Debate over Surnames vs. Patronymics in Iceland - Willson Kendra (Switzerland, 2026)
Iceland stands out in today’s Europe due to the fact that most Icelanders use patronymics rather than surnames. However, a small percentage of Icelanders do have surnames inherited in a fixed form. The first surnames were adopted in the 17th and 18th centuries. In the late 19th and early 20th centuries, increasing numbers of Icelanders were taking up surnames, often Danicized or Latinized versions of Icelandic patronymics or place names. The practice became controversial with the rise of the independence movement, which was closely connected to linguistic purism. The use of surnames in Iceland has been debated since the 19th century. Whereas the other Nordic countries introduced legislation requiring citizens to have surnames, Iceland went in the opposite direction, forbidding new surnames starting in 1925. However, the surnames that were already in use were allowed to remain in circulation. This created an inequality which has haunted Icelandic name law discourse since. Having a surname in Iceland has often been linked with social prestige, and surnames have been perceived as a limited good. Since the 1990s, the fraction of Icelanders with surnames has increased through immigration and some liberalizations in the rules regarding the inheritance of existing Icelandic surnames. In the name of gender equity, surnames can be inherited along any line, not only patrilineal. Since 1996, immigrants seeking Icelandic citizenship are no longer required to change their names, and their children can inherit their surnames. The category of millinöfn (middle name), surname-like names that are not inflected for gender, was introduced in the 1996 law; some Icelanders with millinöfn use them as surnames in daily life even if they officially have patronymics. Despite the expansion in eligibility to take surnames, the basic principle that no new Icelandic surnames are allowed remains in the law and remains a point of contention. Many of the same themes—individual freedom vs. the preservation of cultural heritage, national vs. international orientation, gender equity—have recurred in the discourse over more than a century, reframed in the context of contemporary cultural values at any given time.